INFLUÊNCIA DE FUNGOS MICORRÍZICOS ARBUSCULARES NO DESENVOLVIMENTO DE PLANTAS DE ALECRIM E MANJERICÃO - Russomanno, O.m.r. (2021)
The aim of this research was to evaluate the influence of AMF Glomus etunicatum Becker & Gerd. and Glomus clarum Nicol. & Schenck on rosemary (Rosmarinus officinalis L.) and basil (Ocimum basilicum L.) plants previously inoculated in the greenhouse. The soil was sterilized and composed of one part sand and one part earth. The inoculum was composed of the fungi spores [500 spores of G. etunicatum in (50 mL-1) soil and 700 spores of G. clarum in (50 mL-1) soil] and micelium and roots fragments infected by the AMF. For each plant inoculated an evaluation was made of: plant height (PH), plant dry weight (PDW), root fresh weight (RFW), sporulation (S) and the mycorrhizal colonization (MC). The experiment was carried out in a completely randomized factorial design with three treatments (GE – G.etunicatum; GC –G. clarum; T – control), with 16 replicates for rosemary and 12 replicates for basil. In the rosemary,G. clarum was more efficient than G. etunicatum in the variables PH (24.15%), PDW (67.16%) and S (48.16%); although G. clarum presented a smaller MC than G. etunicatum. In relation to the control, G. clarum was better for the plants in regard to all the variables, although G. etunicatum did not differ for the control plants in PH and PDW. For basil in all the analised variables G. clarum differed from control and from G. etunicatum, which was similar to the control treatment in all the variables, except in the MC and S. In relation to the control, G. clarum was better for the basil in regard to PH (45.49%) and PDW (93.10%).